Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides